2012
DOI: 10.1021/jf204909p
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Xanthohumol, a Prenylated Flavonoid from Hops (Humulus lupulus), in Ischemic Stroke of Rats

Abstract: Xanthohumol is the principal prenylated flavonoid in hops (Humulus lupulus L.), an ingredient of beer. Xanthohumol was found to be a potent chemopreventive agent; however, no data are available concerning its neuroprotective effects. In the present study, the neuroprotective activity and mechanisms of xanthohumol in rats with middle cerebral artery occlusion (MCAO)-induced cerebral ischemia were examined. Treatment with xanthohumol (0.2 and 0.4 mg/kg; intraperitoneally) 10 min before MCAO dose-dependently atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 40 publications
2
53
0
Order By: Relevance
“…Furthermore, XN treatment significantly improved blood viscosity in rats. These results suggest that XN may have great potential as an anti-thrombotic drug and are consistent with published reports stating that beer at moderate levels may protect against thrombosis and XN reduce infarct volume in rats with cerebral ischemia [10,11,51]. A well-known major limitation of current antithrombotic therapies is their inability to separate bleeding occurrences from thrombotic events as well as various serious side effects [6].…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, XN treatment significantly improved blood viscosity in rats. These results suggest that XN may have great potential as an anti-thrombotic drug and are consistent with published reports stating that beer at moderate levels may protect against thrombosis and XN reduce infarct volume in rats with cerebral ischemia [10,11,51]. A well-known major limitation of current antithrombotic therapies is their inability to separate bleeding occurrences from thrombotic events as well as various serious side effects [6].…”
Section: Discussionsupporting
confidence: 88%
“…Xanthohumol is a prenylated calconoid that is a part of the flavonoid family. Treatment with xanthohumol has been shown to be neuroprotective in stroke-induced rats [69]. Recent evidence found that derivatives of xanthohumol can induce neurite growth in mouse neuronal cells [70].…”
Section: Discussionmentioning
confidence: 99%
“…24 PYC is a patented combination of bioflavonoids extracted from the bark of French maritime pine tree (Pinus maritima) and has a high capacity to scavenge free radicals and promote cellular health. Bioflavonoids are natural compounds that are known as neuroprotective agents, due in part to their antioxidant and antiinflammatory properties 25 and their ability to modulate intracellular signaling. 26 In our previous study, animals were treated with multiple high intraperitoneal doses of PYC immediately after the trauma.…”
Section: Journal Ofmentioning
confidence: 99%